ENVIRONMENTAL SUSTAINABILITY PRACTICES IN THE HOSPITALITY INDUSTRY (CASE STUDY: FOUR STARS AND FIVE STARS HOTELS IN MANADO) - Voges, Nadine N; Tulung, Joy E.; Tielung, Maria V. J. (Universitas Sam Ratulangi, 2020)
Abstract: At this time, the environment is getting worse. There are many people who really care to take the role of improving the environment, and there are still many people who do not care, or accustomed to and accidentally damage the environment. Environmental sustainability is concerned with whether environmental resources will be protected and maintained for future generations. Not only by littering, people do not realize that the company is wasting too much natural resources, or producing a lot of pollution. Hospitality industry is one of the polluting industry that caused environmental damage. Business has always depended on, and had an impact on the natural world. Businesses affect the environment through the extraction and utilisation of environmental resources, and through pollution that is released through the processes. The objective of this research is to find out how is the environmental sustainability in 4 and 5 stars hotels in Manado. This research used qualitative analysis. The population in this research refers to the managers of the 4 and 5 stars hotels in Manado and samples used in this study of 6 informants. Finding of this research shows that the hospitality industry in Manado do some practices towards environmental sustainability, but some have not. The hotels should keep improving their practices to do more about preventing environmental damage. There is no loss in this matter. Maybe for some aspects, hotel must spend some money for it, but thatâ€™s how the hotel gaining competitive advantages and risk management.Â Â Keyword: Environmental Sustainability, Hospitality Industry, Business, Environment